Peningkatan Motivasi Belajar Siswa Menggunakan Media Visual Powerpoint - Halimah Tusa’Diah; Anggi Septia Nugroho; Arizal Eka Putra (STAI AL-AMIN, 2025)
This study focuses on the low motivation of students in learning Islamic Education (PAI) subject in Grade V at SDN 1 Kalibalau Kencana, Bandar Lampung. Several students appear to be less enthusiastic and lack enthusiasm in participating in the learning process. To address this issue, the teacher implements the use of visual media to enhance students' motivation to learn. The aim of this research is to determine how the use of visual media can be employed to improve students' motivation in learning PAI in Grade V. This study adopts a qualitative approach with data collection methods including interviews, observations, and documentation. The data analysis process is carried out through reduction, data presentation, and conclusion drawing stages. The results show that the use of PowerPoint visual media can create a more engaging and interactive learning environment. This encourages students to be more active during lessons. The learning process begins with opening activities such as greetings, prayer, attendance check, and ice-breaking. Next, the teacher delivers the material on Asmaul Husna using visual media. At the end of the lesson, the teacher and students collaboratively summarize the material and conduct a question-and-answer session. This approach effectively boosts students' motivation and involvement in the PAI learning process.